Modification of the properties of aircraft engine compressor blades by uninterrupted and pulsed-ion beams - Shulov V. A.; Nochovnaya N. A.; Ryabchikov A. I. Aleksandr Ilyich; Remnev G. E. Gennady Efimovich (1997, 1997)
Title screen